The Transmission of Terrorist Movements in Sulawesi through the Narrative of the Islamic State of DI/TII (1953-1965) - Ahmad Subair (INFOKUM, 2026)
This study analyses the transmission of the narrative of the Darul Islam/Indonesian Islamic Army (DI/TII) movement in Sulawesi led by Kahar Muzakkar (1953–1965) into the ideology of contemporary terrorist groups in the region. Using historical methods within a Systematic Literature Review (SLR) framework, the study reveals the mechanisms of transmission through kinship networks, informal education, and the circulation of literature that mythologises the history of this resistance. The findings show that the DI/TII narrative has been adapted and synthesised with transnational ideologies such as ISIS, resulting in historical-emotional legitimacy for groups such as Mujahidin Indonesia Timur (MIT). This process of ‘glocalisation of jihad’ confirms that counter-terrorism approaches in Sulawesi must critically consider the historical roots and memory of local conflicts, in addition to countering global narratives.